(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the critical role of articles (a, an, the) in English grammar, emphasizing their significance from a learner’s perspective. It highlights common difficulties faced by non-native English speakers, particularly those whose native languages lack an article system, such as Russian, Chinese, or Uzbek. The study investigates how article usage affects overall sentence clarity, fluency, and accuracy in both spoken and written English. Through a review of existing literature and classroom-based observations, the paper outlines effective teaching strategies to enhance learners’ understanding and proper use of articles. The findings suggest that explicit instruction, contextualized practice, and contrastive analysis can significantly improve article acquisition among ESL learners.